Modified polyvinyl alcohol composite material as well as preparation method and application thereof

By combining p-aldehyde benzoic acid modified polyvinyl alcohol and melamine borate, a two-phase network structure is formed, which solves the problem of degradation of mechanical properties of polyvinyl alcohol materials in high humidity environments, and achieves high fracture strength, toughness and Water resistance, suitable for packaging, construction and other fields.

CN119119663APending Publication Date: 2024-12-13BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411388085.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The mechanical properties of existing polyvinyl alcohol materials are deteriorated in high humidity environments, making it difficult to have good water resistance and mechanical properties. Crosslinking modification increases the brittleness of the material, and nanofillers are prone to agglomeration and affect uniformity and mechanical properties.

Method used

Using a combination of para-aldehyde benzoic acid modified polyvinyl alcohol and melamine borate, a biphasic network structure is formed through acetal reaction and self-assembly to enhance the strength and toughness of the material, and to improve the fiber and the interaction between hydrogen bonds and π-π Interface adhesion of the substrate.

Benefits of technology

The fracture strength, fracture toughness and crystallinity of polyvinyl alcohol composite materials are improved, their application performance in high humidity environments and flame retardant performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119663A_ABST
    Figure CN119119663A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polyvinyl alcohol materials, and particularly relates to a modified polyvinyl alcohol composite material as well as a preparation method and application thereof. The modified polyvinyl alcohol composite material provided by the invention comprises p-formylbenzoic acid modified polyvinyl alcohol and melamine borate, the p-formylbenzoic acid modified polyvinyl alcohol is obtained by carrying out aldolization reaction on polyvinyl alcohol and p-formylbenzoic acid, and the molar ratio of the polyvinyl alcohol to the p-formylbenzoic acid is 1: (0.05-0.40); the mass percentage content of melamine borate in the modified polyvinyl alcohol composite material is 1-30%. The modified polyvinyl alcohol composite material provided by the invention has good mechanical properties in a high-humidity environment, overcomes the problem of insufficient mechanical strength caused by low crystallinity of an existing polyvinyl alcohol-based material, and expands the application range of the modified polyvinyl alcohol composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyvinyl alcohol materials, and in particular relates to a modified polyvinyl alcohol composite material and a preparation method and application thereof. Background Art

[0002] Polyvinyl alcohol (PVA) is a widely used synthetic polymer that can be used to prepare films and materials. It has good film-forming properties, adhesion, emulsification and oil resistance. In addition, polyvinyl alcohol is a widely used water-soluble polymer with extremely strong hydrophilicity and water solubility. Due to this hydrophilicity and water absorption, polyvinyl alcohol materials are greatly affected by humidity and moisture in the use environment. In high humidity or water environments, their mechanical properties are greatly reduced or even unusable. Effectively improving the water resistance of polyvinyl alcohol materials can expand their scope of use and realize the value of the wide application of polyvinyl alcohol materials.

[0003] At present, the methods used to improve the mechanical properties of polyvinyl alcohol in high humidity environments are mainly to form a cross-linked network structure by adding boric acid, glutaraldehyde, etc. or to introduce nanofillers into the polymer to compound the polymer with high-strength fibers. Although these methods can effectively improve the mechanical properties of polyvinyl alcohol materials in aqueous environments, they also have some defects and shortcomings; for example, cross-linking modification often increases the brittleness of the material, reduces toughness and ductility, and affects its practical application performance; nanofillers are easy to agglomerate, affecting the uniformity and mechanical properties of the material; the interface adhesion between the fiber and the matrix is ​​insufficient, and delamination is prone to occur. Therefore, providing a polyvinyl alcohol material with good water resistance and mechanical properties is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, the present invention provides a modified polyvinyl alcohol composite material and a preparation method and application thereof. The composite material prepared by the present invention has good water resistance and mechanical properties, and has high fracture strength and fracture toughness in a high humidity environment, thereby expanding its application range.

[0005] In order to solve the above technical problems, the present invention provides a modified polyvinyl alcohol composite material, comprising p-formylbenzoic acid modified polyvinyl alcohol and melamine borate;

[0006] The p-formylbenzoic acid-modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, wherein the molar ratio of the polyvinyl alcohol to the p-formylbenzoic acid is 1:0.05-0.40;

[0007] The mass percentage of melamine borate in the modified polyvinyl alcohol composite material is 1-30%.

[0008] Preferably, the preparation method of melamine borate comprises the following steps:

[0009] Melamine and boric acid are dissolved in water and then allowed to stand to obtain the melamine borate.

[0010] Preferably, the molar ratio of melamine to boric acid is 1:1.8-2.2.

[0011] Preferably, the dissolution temperature is 85-95°C and the dissolution time is 25-35 min;

[0012] The standing temperature is 10-30° C. and the standing time is 12-24 hours.

[0013] Preferably, the preparation method of the p-formylbenzoic acid modified polyvinyl alcohol comprises the following steps:

[0014] The p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution are mixed for acetalization reaction and then mixed with methanol for precipitation to obtain the p-formylbenzoic acid modified polyvinyl alcohol.

[0015] Preferably, the molar ratio of polyvinyl alcohol to p-formylbenzoic acid in the system obtained by mixing the p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution is 1:0.05-0.40;

[0016] The solvent of the polyvinyl alcohol solution includes dimethyl sulfoxide, N,N-dimethylacetamide or glycerol; the mass concentration of the polyvinyl alcohol solution is 8-12%;

[0017] The molar concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L;

[0018] The mass ratio of the polyvinyl alcohol solution to the hydrochloric acid solution is 38-42:1;

[0019] The temperature of the acetalization reaction is 70-80° C. and the time is 12-24 hours.

[0020] The present invention also provides a method for preparing the modified polyvinyl alcohol composite material described in the above technical solution, comprising the following steps:

[0021] The p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate and an organic solvent are mixed to obtain a mixed solution;

[0022] The mixed solution is molded to obtain the modified polyvinyl alcohol composite material.

[0023] Preferably, the organic solvent includes dimethyl sulfoxide, N,N-dimethylacetamide or glycerol;

[0024] The mass ratio of the p-formylbenzoic acid modified polyvinyl alcohol to melamine borate is 70:30 to 99:1.

[0025] Preferably, the forming method includes coating into film or spinning into fiber.

[0026] The present invention also provides the use of the modified polyvinyl alcohol composite material described in the above technical solution or the modified polyvinyl alcohol composite material prepared by the preparation method described in the above technical solution in packaging bags, shopping bags, garbage bags, textiles, building materials or automobile shells.

[0027] The present invention provides a modified polyvinyl alcohol composite material, comprising p-formylbenzoic acid modified polyvinyl alcohol and melamine borate; the p-formylbenzoic acid modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, the molar ratio of polyvinyl alcohol to p-formylbenzoic acid is 1:0.05-0.40; the mass percentage of melamine borate in the modified polyvinyl alcohol composite material is 1-30%. The modified polyvinyl alcohol composite material provided by the present invention has the following advantages: (1) The present invention constructs an interpenetrating two-phase network structure between soft and hard phases by introducing rigid melamine borate rich in hydrogen bonds into flexible modified polyvinyl alcohol. The hard phase in the network structure provides rigidity and strength for the material, while the soft phase provides toughness and energy dissipation pathways, thereby improving the overall strength of the material, effectively dispersing and transmitting stress, reducing the occurrence of plastic deformation, and the prepared film has a fracture strength of up to 163.3MPa. (2) During the material preparation process, melamine borate self-assembles into a micron-sized fibrous structure based on hydrogen bonding interactions. When subjected to load, this structure exhibits pull-out and interfacial debonding effects in the material, thereby achieving toughening properties similar to those of fiber composites, thereby improving the ductility and toughness of the modified polyvinyl alcohol composite material. (3) The micron-sized fibrous structure formed by the self-assembly of melamine borate is tightly bonded to the modified polyvinyl alcohol matrix through non-covalent bonds such as hydrogen bonding and π-π interactions. These supramolecular interactions enhance the interfacial adhesion between the fiber and the polymer matrix. During stretching and impact, it provides an energy dissipation pathway, can effectively transfer stress, and prevent debonding and rupture at the interface, thereby improving the overall toughness of the material. The fracture toughness of the prepared film can reach 143.2MJ / m 3 (4) Melamine borate can induce an increase in the crystallinity of modified polyvinyl alcohol. As a nucleating agent, melamine borate can provide heterogeneous nucleation points, thereby promoting the orderly arrangement and crystallization process of polyvinyl alcohol molecular chains. The introduction of nucleating agents can reduce the nucleation energy barrier, making it easier to crystallize at lower temperatures, thereby increasing its crystallinity. The crystallinity of the prepared film is increased to 35.7%, giving the material better moisture resistance.

[0028] In addition, melamine borate has flame retardant properties and can effectively improve the flame retardant properties of modified polyvinyl alcohol composites. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the melamine borate prepared in Example 1;

[0030] Figure 2 F prepared in Example 4 20 SEM images of the films;

[0031] Figure 3 F prepared in Example 4 20 Atomic force microscopy phase images of thin films;

[0032] Figure 4 The differential scanning calorimetry spectra of the thin film materials prepared in Example 4 and Comparative Examples 1-2;

[0033] Figure 5 F prepared in Example 4 20 In-situ variable temperature infrared spectrum of the film;

[0034] Figure 6 XRD spectra of thin film materials prepared in Example 4 and Comparative Examples 1-2;

[0035] Figure 7 The stress-strain diagrams of the thin film materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2;

[0036] Figure 8 F prepared in Example 4 20 Photo of the film being pulled with a weight after being soaked in water for 12 hours. DETAILED DESCRIPTION

[0037] The invention provides a modified polyvinyl alcohol composite material, comprising p-formylbenzoic acid modified polyvinyl alcohol and melamine borate;

[0038] The p-formylbenzoic acid-modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, wherein the molar ratio of the polyvinyl alcohol to the p-formylbenzoic acid is 1:0.05-0.40;

[0039] The mass percentage of melamine borate in the modified polyvinyl alcohol composite material is 1-30%.

[0040] In the present invention, unless otherwise specified, all raw materials are conventional commercially available products.

[0041] As a specific embodiment of the present invention, the preparation method of the p-formylbenzoic acid modified polyvinyl alcohol (PVA-CBA) may include the following steps:

[0042] The p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution are mixed for acetalization reaction and then mixed with methanol for precipitation to obtain the p-formylbenzoic acid modified polyvinyl alcohol.

[0043] As a specific embodiment of the present invention, the solvent of the p-formylbenzoic acid solution may include dimethyl sulfoxide (DMSO), N,N-dimethylacetamide or glycerol, which may be dimethyl sulfoxide; the mass concentration of the p-formylbenzoic acid solution may be 5-10%.

[0044] As a specific embodiment of the present invention, the solvent of the polyvinyl alcohol solution may include dimethyl sulfoxide, N,N-dimethylacetamide or propylene glycol, and may be dimethyl sulfoxide; the mass concentration of the polyvinyl alcohol solution may be 8-12%, and may be specifically 8%, 10% or 12%.

[0045] As a specific embodiment of the present invention, the molar concentration of the hydrochloric acid solution can be 0.8-1.23 mol / L, specifically 1 mol / L; the mass ratio of the polyvinyl alcohol solution to the hydrochloric acid solution can be 38-42:1, specifically 40:1.

[0046] As a specific embodiment of the present invention, the molar ratio of polyvinyl alcohol to p-formylbenzoic acid in the system obtained by mixing the p-formylbenzoic acid solution, polyvinyl alcohol solution and hydrochloric acid solution can be 1:0.05-0.40, or 1:0.1-0.3.

[0047] As a specific embodiment of the present invention, the mixing comprises the following steps:

[0048] Ultrasonic dispersion of p-formylbenzoic acid in a solvent to obtain a p-formylbenzoic acid solution;

[0049] The p-formylbenzoic acid solution is added dropwise to the polyvinyl alcohol solution and then the hydrochloric acid solution is added.

[0050] As a specific embodiment of the present invention, the temperature of the acetalization reaction can be 70-80°C, specifically 70°C, 75°C or 80°C; the time of the acetalization reaction can be 12-24h, specifically 12h, 15h, 17h, 20h, 22h or 24h.

[0051] The present invention has no special requirement on the amount of methanol used, and the precipitation can be carried out in a conventional manner in the art.

[0052] As a specific embodiment of the present invention, the preparation method of melamine borate comprises the following steps:

[0053] Melamine and boric acid are dissolved in water and then allowed to stand to obtain the melamine borate.

[0054] As a specific embodiment of the present invention, the molar ratio of melamine to boric acid can be 1:1.8-2.2, specifically 1:2. As a specific embodiment of the present invention, the water can be deionized water; the dissolution temperature can be 85-95°C, specifically 85°C, 90°C or 95°C; the dissolution time can be 25-35min, specifically 25min, 30min or 35min. As a specific embodiment of the present invention, the dissolution can be accompanied by stirring.

[0055] As a specific embodiment of the present invention, the standing temperature can be 10-30°C, specifically 20°C, 25°C or 30°C; the standing time can be 12-24h, or 18-20h. In the present invention, the melamine and boric acid are salted by standing.

[0056] As a specific embodiment of the present invention, the standing may further include: filtering the system after standing, washing and drying the solid obtained by the filtration in sequence to obtain the melamine borate. The present invention has no special requirements for the filtration and can adopt the conventional methods in the art. As a specific embodiment of the present invention, the water for washing can be deionized water, the temperature of the water for washing can be 0 to 10°C, and the number of times of washing can be 2 times, 3 times or 4 times. As a specific embodiment of the present invention, the drying can be freeze-drying.

[0057] In the present invention, the mass percentage of melamine borate in the modified polyvinyl alcohol composite material is 1 to 30%, can be 3 to 20%, and can also be 5 to 15%.

[0058] In the present invention, the modified polyvinyl alcohol composite material can be a modified polyvinyl alcohol composite material film or a modified polyvinyl alcohol composite material fiber; the thickness of the modified polyvinyl alcohol composite material film can be 0.1 to 100 μm, or 1 to 80 μm; the modified polyvinyl alcohol composite material fiber has better toughness than the modified polyvinyl alcohol composite material film.

[0059] The present invention also provides a method for preparing the modified polyvinyl alcohol composite material described in the above technical solution, comprising the following steps:

[0060] The p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate and an organic solvent are mixed to obtain a mixed solution;

[0061] The mixed solution is molded to obtain the modified polyvinyl alcohol composite material.

[0062] The present invention mixes p-formylbenzoic acid modified polyvinyl alcohol, melamine borate and an organic solvent to obtain a mixed solution. As a specific embodiment of the present invention, the organic solvent may include dimethyl sulfoxide, N,N-dimethylacetamide or propylene glycol, and may be specifically dimethyl sulfoxide; the mass ratio of the p-formylbenzoic acid modified polyvinyl alcohol and melamine borate may be 70:30 to 99:1, and may be specifically 99:1, 97:3, 95:5, 85:15, 80:20 or 70:30.

[0063] As a specific embodiment of the present invention, the mixing may include the following steps:

[0064] dissolving p-formylbenzoic acid-modified polyvinyl alcohol in a portion of an organic solvent to obtain a p-toluic acid-modified polyvinyl alcohol solution;

[0065] dissolving melamine borate in the remaining portion of the organic solvent to obtain a melamine borate solution;

[0066] The melamine borate solution is added dropwise to the p-toluic acid-modified polyvinyl alcohol solution.

[0067] The present invention has no particular limitation on the volume percentage of the partial organic solvent to the total organic solvent, as long as it can be completely dissolved.

[0068] The present invention has no special requirements for the dropwise addition, as long as it can be added dropwise.

[0069] After obtaining the mixed solution, the present invention shapes the mixed solution to obtain the modified polyvinyl alcohol composite material. As a specific embodiment of the present invention, the shaping method may include coating to form a film or spinning to form a fiber. The present invention forms a modified polyvinyl alcohol composite film by coating to form a film, and forms a modified polyvinyl alcohol composite fiber by spinning to form a fiber.

[0070] As a specific embodiment of the present invention, the preparation method of the modified polyvinyl alcohol composite film comprises the following steps: applying the mixed solution to the surface of the substrate and curing it to obtain a modified polyvinyl alcohol composite film. As a specific embodiment of the present invention, the material of the substrate may include glass plate, polypropylene (PP), polyvinyl chloride (PVC), polycarbonate (PC), aluminum or stainless steel; the present invention may pre-treat the substrate before the coating, and when the substrate is a glass plate, the pre-treatment may be plasma treatment. As a specific embodiment of the present invention, the coating may be scraping; the curing temperature may be 65 to 75°C, specifically 65°C, 70°C or 75°C; the curing time may be 12 to 24h, and may also be 15 to 20h. After the curing, the present invention may also peel off the cured film material from the substrate surface and dry it to obtain a modified polyvinyl alcohol composite film; the drying may be vacuum drying.

[0071] As a specific embodiment of the present invention, the preparation method of the modified polyvinyl alcohol composite fiber can be wet spinning, and the coagulation bath of the wet spinning can be methanol. The present invention washes and then stretches the fiber obtained by wet spinning. The present invention can remove the solvent remaining on the surface of the fiber after washing. The present invention has no special requirements for the washing and stretching, and the conventional methods in the art can be used.

[0072] The present invention also provides the use of the modified polyvinyl alcohol composite material described in the above technical solution or the modified polyvinyl alcohol composite material prepared by the preparation method described in the above technical solution in packaging bags, shopping bags, garbage bags, textiles, building materials or automobile shells. As a specific embodiment of the present invention, the modified polyvinyl alcohol composite film can be used to prepare packaging bags, shopping bags or garbage bags; the modified polyvinyl alcohol composite fiber can be used to prepare textiles, building materials or automobile shells.

[0073] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0074] Example 1

[0075] (1) Preparation of PVA-CBA

[0076] Dissolving polyvinyl alcohol in dimethyl sulfoxide to obtain a polyvinyl alcohol solution with a mass concentration of 10%;

[0077] Dissolving p-formylbenzoic acid in dimethyl sulfoxide to obtain a p-formylbenzoic acid solution with a mass concentration of 5%;

[0078] 50 mL of p-formylbenzoic acid solution was added dropwise into 200 mL of polyvinyl alcohol solution, and then 5 mL of hydrochloric acid solution with a molar concentration of 1 mol / L was added. The mixed solution (the molar ratio of polyvinyl alcohol and p-formylbenzoic acid in the mixed solution was 1:0.30) was subjected to acetal reaction at 75°C (with stirring) for 24 hours, and then precipitated in methanol to obtain p-formylbenzoic acid-modified polyvinyl alcohol PVA-CBA.

[0079] (2) Preparation of melamine borate

[0080] Melamine and boric acid were dissolved in 50 mL of deionized water at a molar ratio of 1:2 (90°C, with stirring), the resulting solution was naturally cooled to 25°C and allowed to stand for 24 hours, filtered, and the filtered solid was washed three times with deionized water at 0°C and freeze-dried to obtain white crystalline melamine borate.

[0081] (3) Preparation of modified polyvinyl alcohol composite film

[0082] Dissolving PVA-CBA in dimethyl sulfoxide to obtain a PVA-CBA solution with a mass concentration of 5%;

[0083] Dissolving melamine borate in dimethyl sulfoxide to obtain a 10 mg / mL melamine borate solution;

[0084] The melamine borate solution was added dropwise to the PVA-CBA solution under stirring to obtain a mixed solution; the mass ratio of the melamine borate to the PVA-CBA in the mixed solution was 1:99;

[0085] The mixed solution was scraped onto the surface of a plasma-treated glass plate and cured at 70°C for 24 hours. The mixed solution was peeled off from the glass substrate and then vacuum dried at 70°C to obtain a modified polyvinyl alcohol composite film, which was denoted as F. 1 film.

[0086] Example 2

[0087] A modified polyvinyl alcohol composite film was prepared according to the method of Example 1, except that the mass ratio of melamine borate to PVA-CBA in the mixed solution was 3:97. The prepared modified polyvinyl alcohol composite film was denoted as F 3 film.

[0088] Example 3

[0089] A modified polyvinyl alcohol composite film was prepared according to the method of Example 1, except that the mass ratio of melamine borate to PVA-CBA in the mixed solution was 5:95. The prepared modified polyvinyl alcohol composite film was denoted as F 5 film.

[0090] Example 4

[0091] A modified polyvinyl alcohol composite film was prepared according to the method of Example 1, except that the mass ratio of melamine borate to PVA-CBA in the mixed solution was 20:80. The prepared modified polyvinyl alcohol composite film was denoted as F 20 film.

[0092] Example 5

[0093] A modified polyvinyl alcohol composite film was prepared according to the method of Example 1, except that the mass ratio of melamine borate to PVA-CBA in the mixed solution was 30:70. The prepared modified polyvinyl alcohol composite film was denoted as F 30 film.

[0094] Example 6

[0095] Prepare a mixed solution according to the method of Example 1;

[0096] The mixed solution is extruded through a spinning pump, and a fine liquid flow is formed through a spinneret. The liquid flow is dripped into a methanol coagulation bath, and after washing and stretching, a modified polyvinyl alcohol composite fiber is obtained.

[0097] Comparative Example 1

[0098] Dissolving polyvinyl alcohol in dimethyl sulfoxide to obtain a polyvinyl alcohol solution with a mass concentration of 5%;

[0099] The polyvinyl alcohol solution was scraped onto the surface of the plasma-treated glass plate, and after curing at 70° C. for 24 hours, it was peeled off from the glass substrate and vacuum dried at 70° C. to obtain a polyvinyl alcohol film, which was recorded as a PVA film.

[0100] Comparative Example 2

[0101] Prepare PVA-CBA according to the method of Example 1;

[0102] Dissolving PVA-CBA in dimethyl sulfoxide to obtain a PVA-CBA solution with a mass concentration of 5%;

[0103] The PVA-CBA solution was scraped onto the surface of a plasma-treated glass plate, and after curing at 70° C. for 24 hours, it was peeled off from the glass substrate and vacuum dried at 70° C. to obtain a PVA-CBA film.

[0104] The melamine borate prepared in Example 1 was examined by scanning electron microscopy to obtain a SEM image. Figure 1 As shown. Figure 1It can be seen that melamine borate self-assembles into micrometer-scale fibrous structures based on hydrogen bonding interactions.

[0105] The F prepared in Example 4 20 The film was tested by scanning electron microscopy to obtain a SEM image, such as Figure 2 As shown. Figure 2 It can be seen that melamine borate has a significant effect on the performance of modified polyvinyl alcohol composite films (F 20 The film shows a fibrous structure.

[0106] The F prepared in Example 4 was examined by atomic force microscopy. 20 The film is tested and a phase diagram is obtained, such as Figure 3 As shown. Figure 3 It can be seen that melamine borate has a significant effect on the performance of modified polyvinyl alcohol composite films (F 20 The film has an interpenetrating two-phase network structure of soft and hard phases.

[0107] Figure 4 The differential scanning calorimetry spectra of the thin film materials prepared in Example 4 and Comparative Examples 1-2 are shown in Table 1. The melting peak area of ​​the crystalline region and the calculated crystallinity value obtained from the DSC spectra are verified by F 20 The film has a high degree of crystallinity.

[0108] Figure 5 is the F prepared in Example 4 20 In-situ variable temperature infrared spectrum of the film, according to Figure 5 Proved that F 20 There are hydrogen bonding interactions inside the film.

[0109] Figure 6 The XRD spectra of the thin film materials prepared in Example 4 and Comparative Examples 1-2 show that the diffraction peak intensity at 2Theta of 20° is high and the half-peak width is narrow, which verifies that F 20 The film has a high degree of crystallinity.

[0110] The film materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to stress-strain testing, and the obtained stress-strain diagrams are shown in FIG. Figure 7 The obtained fracture strength, Young's modulus, fracture elongation and fracture toughness results are listed in Table 1.

[0111] Table 1 Mechanical properties of the film materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2

[0112]

[0113] Combining Table 1 and Figure 7 It can be seen that the modified polyvinyl alcohol composite material provided by the present invention has higher tensile strength and toughness.

[0114] The F prepared in Example 4 20 After the film was immersed in water for 12 hours, Figure 8 The weight of 250g is steadily lifted by the method, and then the weight of the weight is increased in the order of 50g each time. When the weight is increased to 750g, F 20 The film will break, which proves that the modified polyvinyl alcohol composite material provided by the present invention has good water resistance.

[0115] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A modified polyvinyl alcohol composite material, characterized in that: Includes p-formylbenzoic acid modified polyvinyl alcohol and melamine borate; The p-formylbenzoic acid-modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, wherein the molar ratio of the polyvinyl alcohol to the p-formylbenzoic acid is 1:0.05-0.40; The mass percentage of melamine borate in the modified polyvinyl alcohol composite material is 1-30%.

2. The modified polyvinyl alcohol composite material according to claim 1, characterized in that: The preparation method of the melamine borate comprises the following steps: Melamine and boric acid are dissolved in water and then allowed to stand to obtain the melamine borate.

3. The modified polyvinyl alcohol composite material according to claim 2, characterized in that: The molar ratio of melamine to boric acid is 1:1.8-2.

2.

4. The modified polyvinyl alcohol composite material according to claim 2 or 3, characterized in that: The dissolution temperature is 85-95°C and the dissolution time is 25-35 minutes; The standing temperature is 10-30° C. and the standing time is 12-24 hours.

5. The modified polyvinyl alcohol composite material according to claim 1, characterized in that: The preparation method of the p-formylbenzoic acid modified polyvinyl alcohol comprises the following steps: The p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution are mixed for acetalization reaction and then mixed with methanol for precipitation to obtain the p-formylbenzoic acid modified polyvinyl alcohol.

6. The modified polyvinyl alcohol composite material according to claim 5, characterized in that: The molar ratio of polyvinyl alcohol to p-formylbenzoic acid in the system obtained by mixing the p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution is 1:0.05-0.40; The solvent of the polyvinyl alcohol solution includes dimethyl sulfoxide, N,N-dimethylacetamide or glycerol; the mass concentration of the polyvinyl alcohol solution is 8-12%; The molar concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L; The mass ratio of the polyvinyl alcohol solution to the hydrochloric acid solution is 38-42:1; The temperature of the acetalization reaction is 70-80° C. and the time is 12-24 hours.

7. The method for preparing the modified polyvinyl alcohol composite material according to any one of claims 1 to 6, comprising the following steps: The p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate and an organic solvent are mixed to obtain a mixed solution; The mixed solution is molded to obtain the modified polyvinyl alcohol composite material.

8. The preparation method according to claim 7, characterized in that: The organic solvent includes dimethyl sulfoxide, N,N-dimethylacetamide or glycerol; The mass ratio of the p-formylbenzoic acid modified polyvinyl alcohol to melamine borate is 70:30 to 99:

1.

9. The preparation method according to claim 7, characterized in that: The forming method includes coating into film or spinning into fiber.

10. Use of the modified polyvinyl alcohol composite material according to any one of claims 1 to 6 or the modified polyvinyl alcohol composite material prepared by the preparation method according to any one of claims 7 to 9 in packaging bags, shopping bags, garbage bags, textiles, building materials or automobile shells.